2D Seismic Imaging Improvement through Prestack Depth Migration (PSDM) Method - Iyod Suherman; Taufan Wiguna; Rahadian Rahadian; Djunaedi Muljawan; Omar Moefti (Institut Teknologi Bandung, 2019)
The quality of seismic is important for interpretation. Prestack Depth Migration produce better quality of seismic imaging. The seismic generated through PSDM method has better seismic reflector and geological structure appearance compared to Prestack Time Migration (PSTM) method. Accurate interval velocity modeling is a key in PSDM process, involving dix transformation, coherency inversion, and tomography. Comparison between PSTM and PSDM show that PSDM offer better imaging for interpretation because PSDM has better seismic reflector continuity and good geological appearance.